Pemaknaan Fanbase Terhadap Isu-Isu Politik Dalam Lagu Bergenre Indie Rock - Ijlal Hibatullah, Alif; Dwiningtyas Sulistyani, Hapsari; Rahardjo, Turnomo (Interaksi Online, 2024)
This research aims to understand how the fanbase of .Feast, an Indonesian indie rock band, interprets political issues conveyed through their songs. Employing a qualitative approach with ethnography of communication method, this study examines the interactions and interpretations of the "Kelelawar" fanbase towards lyrics containing political and social messages. Through content analysis and in-depth interviews, this study reveals that the .Feast fanbase perceives these songs not just as artistic expressions but also as means for political education and empowerment. This perception is reflected in various interpretive codes identified, including codes of political awareness, social responsibility, and artistic expression. The findings demonstrate that .Feast's indie rock music serves as a medium for the fanbase to express and reinforce their collective identity that is critical of the political and social conditions. This research provides new insights into the role of music in shaping political and social consciousness, particularly among the young generation in Indonesia.